Increasing The Mobility Of The Spine In 14-16 Year-Old Children With Scoliosis - Norboev, Ahmad (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
In our civilized society, the majority of children live without leaving their homes. One of the reasons for the curvature of the spine is improper nutrition, they do not know how to walk, stand, sit correctly, and are deprived of full physical activity. We are talking about schoolchildren, the so-called television generation. From the first day at school, the child’s spine is exposed to a heavy load. Inactivity, improper physical education, uncomfortable equipment (furniture), lack of proper posture - all this leads to a deterioration of the musculoskeletal system.